ANTICANCER ACTIVITIES AND METABOLITE FINGERPRINTING OF UPLC-QToF-MS/MS METHOD FROM Chrysanthemum cinerariifolium (Trev) - Listiyana, Anik; Lestari, Nia Ayu; Irawati, Santia; Indrawijaya, Yen Yen Ari; Annisa, Rahmi; Bhagawan, Weka Sidha; Mutiah, Roihatul; Ma'arif, Burhan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Chrysanthemum cinerariifolium (C. cinerariifolium) is an empirically proven medicinal plant that has anticancer activities. This study aimed to profile metabolites, and cytotoxic activity of root, leaf, stem, and root extracts C. cinerariifolium on T47D cells and to determine the correlation of metabolite content with cytotoxic activity. The metabolite profile was carried out using UPLC-QToF-MS / MS, and cytotoxic activity was carried out using the MTT method. The results obtained in the form of a chromatogram were processed with the application Masslynk so that a metabolite profile data obtained. The data is then analyzed statistically using Principal Component Analysis (PCA). The results obtained on metabolite profiling showed that there were differences in metabolite profiles in the roots, stems, leaves, and chrysanthemums. The characteristic compounds in the flower section are D - (-) - Morphine and in the leaf part of genistein Â and N - [(5-Chloro-1,2,3-thiadiazol-4-yl) methyl] -1- (2-isopropyl-4 -methyl-1,3-thiazol-5-yl) -N-methyl ethanolamine. The major compounds in the roots, stems, and leaves are Orphenadrine with successive percentages of 9.11%, 10.16%, and 3.24%, and the major compounds in the flower section are D - (-) - Morphine with a percentage of 10, 86%. Furthermore, the results of the cytotoxic activity test showed differences in anticancer cytotoxic activity in the parts of the flower, leaf, stem, and root of C. cinerariifolium. Besides, there is a relationship between the metabolite content and anticancer cytotoxic activity of each part of C. cinerariifolium. The higher the level of orphenadrine compounds in the plant, the higher the potential for anticancer.Â Keywords: C. cinerariifolium, UPLC-QToF-MS/MS, T47D cells.